Pengaruh Stres Kerja dan Konflik Kerja Terhadap Kinerja Karyawan - Zaynuri, Muhammad; Nur Hotimah, Raisah; Fatikasari, Riska; Aulia Rahman, Syahdilla; Nurarifah, Syifa; Fauzi, Achmad (Jurnal Ilmu Multidisiplin, 2023)
Labor productivity can be regarded as the most important factor that supports the success of the company in achieving its various goals. For companies, labor is considered as an important factor that plays a role as the main factor or the main determining factor in the movement of production activities in the company. Work stress and work conflict are two problems that are often faced by many employees. Job stress can affect a person's physical and psychological condition which in turn threatens the employee's performance. If the problem is not immediately resolved and allowed to drag on, it will affect the quality of the workforce in carrying out their work. The purpose of writing this journal is to find out whether there is an influence between work stress and work conflict on performance. The method used in this research is qualitative and literature study. The results of the analysis show that: 1) There is a positive influence between work stress on employee performance; and 2) There is a positive influence between work conflict on employee performance.